A nationwide analysis of desmoplastic small round cell tumor. Issue 30 (24th July 2020) - Xiang, Tao; Zhang, Shu-Yang; Wang, Sai-Sai; Fei, Ru-Shan; Li, Hui
Abstract : Abstract: This study aim is to enhance the understanding, diagnosis and treatment of desmoplastic small round cell tumor (DSRCT) and to determine what factors can affect survival of the disease in China. We report here 8 patients with DSRCT in our center who received a variety of treatment methods. By reviewing the literature published from Chinese database (CNKI, WANGFAN, VIP, CBM, CMCC) in 2000 to 2015 with the terms of "dsrct", "desmoplastic" and "small round-cell tumor", 104 eligible cases of DSRCT(including 8 cases in our hospital) were retrospectively analyzed. Among the 104 patients, Median age was 24 years with a range of 15 to 54 years. The main primary tumor site was the abdomen and/or pelvis in 92/104 patients (88.5%). Only 25% of patients had localized disease. Most of the patients had received adjuvant chemotherapy (87.5%) and 76.9% patients had not experienced adjuvant radiotherapy. One-fourth of the patients underwent grossly complete surgical resection, and 33.7% and 41.3% patients received no surgery and incomplete surgical resection, respectively. Median overall survival for all patients was 26 months (95% CI: 20.29–31.71). Multivariate analysis revealed that Metastatic status (HR: 2.327, 95% CI: 1.136–4.768, P = .021), Surgical patterns (HR: 0.673, 95% CI: 0.487–0.928, P = .016), and Adjuvant chemotherapy (HR: 0.337, 95% CI: 0.167–0.678, P = .002) were significant independent prognostic factors for longer overall survival. It was noteworthy that CD99 were significantly associated with OS ( P = .002). Here, we identified the prognostic factors which may facilitate risk-adapted treatments for this rare DSRCT group, which should be further investigated.